Beyond Flexibility — Workflows in the perioperative Sector of the Healthcare Domain - Bandt, Markus; Kühn, Robert; Schick, Sebastian; Meyer, Holger (Electronic Communications of the EASST, 2011)
The OR environment of a hospital demands high standards of both qualitative and economic management. Since the basic perioperative processes are rather well defined, the use of WfMS to support the planning and coordination of surgical treatment can be beneficial. The analysis of the perioperative work showed the need of flexibility at certain points in the processes. Within the project PERIKLES a corresponding YAWL model was implemented using several workflow flexibility concepts. A major challenge in this context was the handling of unpredictable exceptions (e.g. changing requirements during surgery). The use of exception handling is one reliable way to meet this requirements.